ASPEK RUANG SEBAGAI LANDASAN PEMILIHAN RUANG DI TEPI LAUT SENGGOL - Shafar, Muhammad Uliah; Wijayanti (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2023)
The increasing of people’s demand on waterfront public space has motivated the waterfront concept that meet the visitor needs. One way to know public space design has met visitor needs is from understanding the preference on public space. Because of those demands, few spaces have emerged in Parepare, one of them is Senggol Beach. Waterfront public space has developed into two distinct spaces. This distinction create a contrast condition which enables people to pick one of the space between them. The huge difference in visitor number potentially creates unbalance to both of spaces. Therefore, Senggol Beach would not be optimal. In this case, public space clearly require the understanding of visitor needs through understanding of their preference. The purpose of this study is to analyze the space aspect which underlying the choice of space in the waterfront. This research method is mixed-method. While, this research design is cross-sectional using cross tabulation and biplot image analysis. Through questionnaire survey, respondents which consist of 85 people were asked to choose one of the spaces which they liked, including their reason to like it according to space aspects. The result shows that 66% respondents like A space and 35% like B space. The reason of many respondents is regarding facilities aspect. Therefore, available designs in B space does not satisfy most respondent’s preference.